90-Day Hospital Readmission Rate in Patients Discharged on Home Non-Invasive Ventilation - Riaz, Rabia; Rehman Malik, Shahzil Abdur; Sarwar Zubairi, Ali Bin (Indus Journal of Bioscience Research, 2025)
Introduction: It is known that home non-invasive mechanical ventilation (NIMV) is gaining traction in the treatment of chronic hypercapnic respiratory failure, which improves quality of life and reduces hospital expenditure. Nevertheless, the problem is a high readmission rate, which creates sick care rather than health care. Objective: To find out the 90-day hospital readmission rate among the patients who were discharged on home NIMV, as well as risk factors, and outcomes. Methods and Materials: This retrospective cohort study used data on the 160 patients on home NIMV discharged in Aga Khan University Hospital, Karachi from 1st January, 2023 to 31st August, 2023. This study utilized data retrieved from electronic health records approved by the Ethical Review Committee. Demographics, comorbidities, and risk factors associated with readmission were analyzed using descriptive statistics as well as multivariate logistic regression. Results: 28.1 percent (45) of 160 patients were readmitted within 90 days. Readmission was predicted by bronchiectasis (OR: 5.18; 95% CI: 1.26-21.30; p = 0.023), prior hospitalization, and frequent follow-ups. There was a longer hospital stay (40%), hospital-acquired infection (17.8%), and 90-day mortality (24.4%) among readmitted patients. Conclusion: The readmission rate is just 28.1%, indicating that it is recommended to implement specific interventions, especially when working with bronchiectasis patients, using airway management and standardized follow-ups to enhance the results.